فعالية نموذج الرؤوس المرقمة في تعليم مهارة الكتابة لدى تلاميذ الصف الثامن في مدرسة نور الشافعية المتوسطة الإسلامية رمفوا - Abdillah, Muhammad Raihan (Penerbit Minhaj Pustaka, 2025)
This study addresses students' difficulties in learning Arabic writing skills, particularly sentence construction. Observations revealed challenges such as limited student engagement, poor cooperation, and low attentiveness. The research aimed to assess the effectiveness of the Numbered Heads Together (NHT) model in improving writing skills and to explore its supporting and inhibiting factors. A mixed-methods approach was used, involving 55 eighth-grade students at MTs Nur Asy-Syafi’iyah Rempoa. Quantitative data were gathered through pre- and post-tests, analyzed using t-tests and N-Gain; qualitative data were analyzed using the Miles, Huberman & Saldana model. The experimental group achieved a higher post-test average (79.40) than the control group (60.03), with a significance level of 0.001, indicating that the NHT model had a significant effect. The N-Gain score of 0.55 showed moderate effectiveness. Factors affecting NHT’s effectiveness included internal aspects—such as motivation, learning styles, and interest—and external aspects like interactive media and the learning environment. Overall, the NHT model proved to be moderately effective in enhancing students’ Arabic writing skills.